YKL-40 and Lysosome-Associated Membrane Proteins as Potential Discriminative Biomarkers in Central Nervous System Infections - Maria Kazakova; Yordan Kalchev; Valentin Dichev; Petya Argirova; Kiril Simitchiev; Mariana Murdjeva; Victoria Sarafian (Microbiology Research)
The aim of our study was to evaluate the discriminative value of gene and protein expression levels of the inflammatory marker (YKL-40) and lysosome-associated membrane protein 1 and 2 (LAMP-1 and LAMP-2) in patients with central nervous system (CNS) infections. Thirty hospitalized patients with CNS infections and undefined etiology, and 22 healthy subjects as a control group, were included in the study. Gene expression levels of YKL-40, LAMP-1 and LAMP-2 were determined by qPCR. Plasma and CSF concentrations of the tree proteins of interest were detected by ELISA. Our results showed that mRNA levels of YKL-40 were significantly downregulated in WBCs of patients compared to controls, while plasma YKL-40 concentrations were higher. LAMP-1 significantly increased in patients’ plasma and CSF was found. Patients were subdivided depending on the confirmed or presumed etiological agent into two subgroups groups—patients with bacterial or with viral neuroinfection. Differences between plasma levels of YKL-40 in the subgroups when matched with controls were detected. The concentrations of the glycoprotein were higher in patients with bacterial infections compared to those with the viral ones. We revealed that LAMP-1 plasma levels were also significantly increased in patients with viral infections in comparison to healthy individuals. We could speculate that YKL-40 plasma levels might serve as a fast discriminative tool to support the presence of viral or bacterial CNS infections.